Embodying the promises of the People Power Revolution public service as civic engagement among millennial officers in a Philippine city jail - Nario-Lopez, Hannah Glimpse (Philippine Social Sciences Review, 2020)
Access online through this link: https://journals.upd.edu.ph/index.php/pssr/article/view/9897/8731